THE SOCIAL AND POLITICAL CONTEXT OF KANT’S RATIONAL SYSTEM - Barbosa, Cloves; Wilson Tafner Junior, Armando (Revista Gênero e Interdisciplinaridade, 2026)
This paper presents the rationnal philosophical Kant’s Sistem with against of philosophical idealisms of Berkeley and Descartes. Berkeley with your panenteism, and Descartes With your egocentrism. Kant’s theorie start of the rationnal sistem with the aprioristic space and time concepts. Kant sustain the idealism that knowlodges are made by rationnal process.